Self-monitoring of Glucose With A Non-invasive Method Using Near Infrared Sensor - Rinda Nur Hidayati; Nur Hasanah Ahniar; Gita Rindang Lestari; Atika Hendryani; Faris Al Hakim (Politeknik Kesehatan Kemenkes Jakarta II, 2020)
Diabetes mellitus or commonly called diabetes is a worldwide epidemic caused by chronic hyperglycemia. Simplify the blood glucose monitoring and easy to use is an essential part of diabetes management. Currently, the use of blood glucose meters conventional in clinical practice needs sufficient reliability. Therefore, self-monitoring of blood glucose with a non-invasive method was presented. A non-invasive blood glucose monitoring device was initially for information on glucose level measurements. A non-invasive method to determine the level of glucose by applying the physical properties of the absorption of the laser sensor that can produce a voltage change at various glucose levels. In this paper, a glucose monitoring module was fabricated with dimensions of 25x27x15 cm which has a minimum system, sensor, and LCD as a display of glucose levels. A minimum system to control the output of data digital value using microcontroller Android nano v.3. Experimentally, testing this module is by comparing the glucose monitoring modules that have been made with a gold standard. The result showed that non-invasive glucose monitoring is the potential for glucose level measurement a sensitivity, resolution, and accuracy of 0.86 mg/dL, 0.01 mg/dL, and 98.96%, respectively. The purposed module of glucose level monitoring offered simple testing for the rapid measurement of glucose levels.